Working Load Analysis at Administration Office of Public Health Center Probolinggo Using WLA Methode - Sandi, Gustian Ari; Tismawati; Haryono (Universitas Panca Marga, 2022)
Analysis of the workload on the office and administration of a Probolinggo city health center needs to be done. Some officers seem to work relaxed while others do not, and some workers do not start work on time and end work early. It appears that in certain sections there is a buildup of work and not in other sections, this seems to be because workers cannot organize work according to a predetermined work schedule. By using workload analysis it can be ascertained that workers have worked well or not. From the results of the analysis it is known that some workers have worked beyond their proper work capacity (overload) and some workers are still working casually.